An introduction to the philosophy of Spinoza - Allison, Henry E. 1937-2023 (Cambridge University Press, 2022)
Aimed at those new to studying Spinoza, this book provides a comprehensive introduction to his thought, placing it in its historical and philosophical contexts, and assessing its critical reception. In addition to providing an analysis of Spinoza's metaphysical, epistemological, psychological, and ethical views in the Ethics, Henry Allison also explores his political theory and revolutionary views on the Bible, as well as his account of Judaism, which led to the excommunication of the young Spinoza from the Jewish community in Amsterdam. Although the book's main focus is on the analysis of Spinoza's views, including a close reading of the central arguments of the Ethics, it also considers many of the standard objections to these arguments as well as possible responses to them. This completely revised and updated new edition of Allison's classic book, with two new chapters, will help a new generation of students to understand and value Spinoza's work
Title from publisher's bibliographic system (viewed on 28 Feb 2022)
Keywords: Spinoza, Benedictus de / 1632-1677; Spinoza, Benedictus de -- 1632-1677; philosophy of Spinoza